Predictors of visual outcome in patients operated for craniopharyngioma – a Danish national study. Issue 1 (29th June 2017) - Jacobsen, Mads Forslund; Thomsen, Ann Sofia Skou; Bach‐Holm, Daniella; Doroudian, Ghazaleh; Nissen, Kamilla Rothe; Fugleholm, Kåre; Poulsgaard, Lars; Siersma, Volkert; Heegaard, Steffen
Abstract: Purpose: Craniopharyngioma often causes visual loss due to the close relation to the anterior visual pathways. This study investigates the incidence and predictors of visual outcomes in patients with craniopharyngioma. Methods: Data from sixty‐six patients who underwent surgery for craniopharyngioma from 2009 to 2013 in Denmark were reviewed. Primary outcomes were visual acuity (VA) and visual field (VF) defects from pre‐and postoperative visits. Secondary outcomes were optic nerve atrophy (OA) and papilledema. Results: Fifty‐eight patients were included. The VA of the patients 1‐year after surgery improved by −0.16 log(MAR) (95%CI: −0.30 to −0.02; p = 0.0266). Visual field (VF) defects worsened in 17 eyes (30%), remained stable in 21 eyes (37%) and improved in 19 eyes (33%). The presence of papilledema and the absence of OA were significantly correlated with an improvement in VA postoperatively (p = 0.011 and p = 0.011, respectively). Patients undergoing surgery within a week or less after their first ophthalmological examination had a significant improvement in VA (−0.36; 95%CI: −0.62 to −0.09; p = 0.0099). Patients undergoing surgery using a subfrontal approach also showed improvement in VA (p = 0.048). Tumour recurrence had a significantly worse VA outcome (p = 0.0074). Conclusion: Patients show a slight improvement in VA 1‐year after operation for craniopharyngioma. The presence of papilledema and early surgical intervention is associated with a significant improvement in VA. Early involvement of a dedicated ophthalmologist is recommended to secure an early detection of a visual decline and potential tumour recurrence.